EPIDEMIOLOGIC STUDY OF ENDOMETRIAL LESION CHARACTERISTICS BY AGE IN PATHOLOGY DIAGNOSTIC CENTER IN SURABAYA 2015-2017 - Sianty Dewi; Imelda Theodora; Bernadette Dian Novita; Yulia Widyasari; Ricardo Gunadi; Maria Amelia Suhardi; Vincentius Diamantino Supit (JURNAL WIDYA MEDIKA, 2021)
Background: The etiology of endometrial lesions varies from benign to malignant. Early detection and management of malignancy give the best prognosis for the patient. While studies in America and Europe report a 3-5% risk of malignancy in women below 50 years and a significant increase up to 75-80% in postmenopausal, the availability of national epidemiologic data is limited, therefore the study is held.Method: A descriptive- retrospective study. Total sampling obtained from endometrial specimens in Pathology Diagnostic Center-Prof JH Lunardhi, Sp.PA(K) from 2015 to 2017, while gestation-related, inadequate sample, and incomplete report are excluded. Data analyzed by IBM SPSS 23.0 version. Result: Data of 560 samples, 90% from curettage, 8% hysterectomy, and 2% hysteroscopy. The majority belonged to the 40-49 age group (44.3%). Secretory phase endometrium is the most common finding in the age group of 20-29 years (26.9%). Proliferative phase endometrium is the most common finding. The highest incidence of endometrial hyperplasia occurred in the age group of 40-49 years, for both typical and non-atypical. Endometrial malignancy was found mostly in the 50-59 years (37.03%). Conclusion: The prevalence of endometrial lesions differed according to age groups, with physiological changes, endometritis, polyps, and hyperplasia were most common under 50 years old and the risk of malignancy increased 4.39 times (p.00) beyond 50 years old.